In the above figure, ABCD and EFGC are squares with areas R and S respectively. What is the area of the gray region?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
S g r e y = ( r 2 + s 2 ) + 2 s ( r − s ) − 2 r ( r + r ) = 2 r 2 + s 2 = 2 S + R
The area of the triangle ADG is R. The area of the triangle BEF is (R-S)/2. So the area of the grey region is R-(R-S)/2=(R+S)/2.
The area of ADG is not R compulsorily. It will be R if and only if R=S. Similarly BEFis not (R-S)/2. The area of ADG is 2 R + R S and the area of BEF is 2 R S − S
Muhammad Abdulla, you are right. My solution is wrong. Thanks for point out my mistake.
Yes that's how i did it. Simple as that
Add a new point H above F so that BHFE is a rectangle, and the area of triangle EFB is half of that rectangle. So the area of the shaded region is (R+S+BHFE)/2 - BHFE/2. That is just (R+S)/2.
Area of triangle ABG = 1/2 area of square ABCD = R/2
Area of triangle BFG = 1/2 area of square EFGC = S/2
By adding
Areaa of the gray region = (R + S)/2
By which theorem Area of 🔺 BFG=1/2 area of squre EFGC
Area of 🔺 BFG=1/2 (FG multilied by FE), a half of (base FG multiplied by height FE). Area of squre EFGC =FG multiplied by FE.
I added an imaginary point "H".
Area of rectangle ADGH: (sqrt(R)+sqrt(S))(sqrt(R)) = R+sqrt(RS)
Area of triangle ADG: 0.5(sqrt(R)+sqrt(S))(sqrt(R)) = 0.5R+0.5sqrt(RS)
Area of triangle BEF: 0.5((sqrt(R)-sqrt(S))(sqrt(S)) = 0.5sqrt(RS)-0.5S
The area of triangle BEF is congruent to the area of triangle BHF.
Find the area of quadrilateral ABFG: (R+sqrt(RS)) - (0.5R+0.5sqrt(RS)) - (0.5sqrt(RS)-0.5S) = 0.5R+0.5S = (R+S)/2
Area of ABFG= Area of ADG - Area of BEF. let AD=a & FG=b. now area of ADG=(a (a+b)/2). area of BEF=((b (a-b)/2). so area of ABFG=(a^2+a b-b a+b^2)/2=(a^2+b^2)/2 a^2=R,b^2=S. so area of ABFG=(R+S)/2
Problem Loading...
Note Loading...
Set Loading...
L e t A B = r a n d E F = s ( s o , R = r 2 a n d S = s 2 ) . A l s o , l e t H b e t h e p o i n t o b t a i n e d b y t h e i n t e r c e p t i o n o f t h e e x t e n t i o n o f t h e s e g m e n t s A B a n d F G ( c l e a r l y , w e h a v e t w o n e w t r i a n g l e s , A H G a n d B H F ) . T h e n : A r e a g r a y = A r e a A H G − A r e a B H F , w h e r e : A r e a A H G = 2 ( r + s ) × r , a n d A r e a B H F = 2 ( r − s ) × s ; T h u s , A r e a g r a y = 2 ( r + s ) × r − 2 ( r − s ) × s = 2 R + S